Evaluation of the perception of smile satisfaction and the influence of digital social media on the population (Research, Society and Development, 2021)
Introduction: The increasing participation of social media in the daily lives of the population has been shaping the way people perceive themselves. Satisfaction with one's own image is built by a mixture of factors intrinsic to one's being and the influences of the external environment, and now, by digital social media. As the Brazilian consumes a lot of digital social media, this exaggerated presence “imposes” new parameters of beauty. Objective: Evaluate the perception of smile satisfaction under the influence of digital social media in the population. Material and method: Descriptive cross-sectional study, qualitative and quantitative approach, with the application of an online questionnaire in the Google Docs format, sent at random to participants through social networks. Results: 171 people responded. The socioeconomic profile mainly comprises women (76%), living in the Northeast region of Brazil (96,5%), incomplete higher education (33,3%), age group 25 to 31 years old (48%), monthly family income of 3 to 5 minimum wages (36,8%), mostly using the digital social networks WhatsApp and Instagram, for more 4h daily (62%). The position of the teeth was the most important characteristic of the smile for 83.6% (n = 143) of the interviewees; 62% (106) would like to make some change in their smile and almost half of the interviewees (47.4%, n = 80) consider that digital social media partially influence the responses attributed to the questionnaire. Conclusion: Respondents stated that they are happy with their smiles, but still want to change something.  The perception of the smile, in general, is influenced by the interviewees' experience in digital social media.